Dos serpúlidos nuevos para .el Pacífico mexicano y duplicidad opercular en Hydroides crucigerus (Polychaeta: Serpulidae)* - de León-González, Jesús Ángel (Universidad de Costa Rica, 1990)
Among samples collected alony the west coast of Baja California Sur, Mexico (AprilI987), aboard B/E MARSEP XIV, calcareous tubes from serpulidae were found adhered to rocks and coral, with a shrimp net, in front of Punta San Juanico and Cabo San Cázaro.